Management of obesity using fuzzy analytic hierarchy process / Norpah Mahat, Fatin Thaqifah Ariff and Siti Sarah Raseli - Mahat, Norpah Mahat; Ariff, Fatin Thaqifah; Raseli, Siti Sarah (Universiti Teknologi MARA, Perlis, 2022)
Obesity has been linked to several heart diseases. Unfortunately, Malaysians today are the most overweight or obese people among Asian nations. That is, half of the population is overweight. There are serious social consequences. Therefore, specific and serious actions are needed to reduce or eliminate this threat. The rapid increase in obesity rates has directed the link with the factors such as low physical activities, ease of transportation, food intake and emotional factor. Thus, this study aims at identifying the most significant factors affecting obesity in Peninsular Malaysia. The factors that are detected to be the cause of obesity can help manage individuals with obesity problems. The fuzzy Analytic Hierarchy Process (F-AHP) approach was used for the identification and ranking of each factor. The method adopted was one of the most reliable methods for both identification and ranking of the most significant factors affecting obesity. The study selected seven respondents and applied the calculations. The calculations consist of seven steps. Initially, the goals and criteria to construct the hierarchy process were determined. This was followed by the distribution of a questionnaire to the respondents using the linguistic scale. After that, two parameters were calculated, these include geometric mean weight and fuzzy weight. Lastly, the fuzzy weight and all the calculations were defuzzified and normalized. The results show the factors that affect obesity the most in Peninsular Malaysia is physical inactivity with a weight of 41.6% after being normalized. Physical inactivity has been ranked the first factor, food intake ranked second, the third rank is an emotional factor and lastly is technology. The precise identification and ranking are very meaningful to the management of the obesity problem. Firstly, there is a need to increase healthy physical activity. Secondly, they need to change their diet according to experts. Lastly, they need to manage their emotions and technology well. This study will enable the public to better understand the causes of obesity and help them to make the proper health adjustment to their lifestyle to achieve better health. The findings from this study also will assist the government in formulating a national health plan to tackle obesity among the public.